Influence of thermal treatment duration on structure and phase composition of additive Co-Cr-Mo alloy samples - Khimich, Margarita A.; Ibragimov, Egor A.; Tolmachev, Alexey I.; Chebodaeva, Valentina V.; Uvarkin, Pavel V.; Saprykina, Natalia A.; Saprykin, Alexander A.; Sharkeev, Yuriy P. 1950- (Письма о материалах)
Laser powder bed fusion (LPBF) requires application of powders with specific characteristics. These are near-spherical shape of particles, uniform elemental composition, typical particle size of 5 - 70 mu m, etc. Such powders are produced by spheroidization methods. They have such disadvantages as high cost and sale only in large quantities. There are publications describing application in LPBF powders, produced by the methods, alternative to spheroidiz,ation. In the current study, powders of pure raw Co, Cr and Mo were used for the production of Co-Cr-Mo powder mixture. Samples of Co-28 wt.% Cr-6 wt.% Mo alloy were produced by LPBF from this powder mixture. Due to the difference between melting temperatures of Co, Cr and Mo, inclusions of Cr and Mo were formed within the bulk of samples. Studies of phase and elemental composition, structure and microhardness of the as-produced samples and after post-treatment with varied duration are represented. As-produced samples have non-uniform elemental composition and are represented by the main Co-based phase. Increasing the annealing duration leads to the sequential dissolution of un-melted Cr and Mo inclusions. Complete dissolution of Cr particles was observed at 10 hours of treatment and complete dissolution of Mo particles was not observed after 20 hours of annealing. Microhardness non-linearly changes with the increasing duration of annealing. This is due to the phase transformations and diffusion processes occurring at such type of post-treatment. Complete dissolution of Mo-particles could be achieved by further increasing the annealing time or by varying the mode of laser powder bed fusion.